Pandemics in ancient Greek and Roman coinage: medical memories at the service of hope. Issue 12 (22nd December 2020) - Iniesta, Ivan
Abstract: Medical goddesses and gods invoked in the Hippocratic Oath were called on in times of pandemics along with Greek physicians such as Galen of Pergamum. Ancient Greek and Roman coinage provide insights into the coexisting religious and rational approaches to medicine rooted in Classical Antiquity, portraying medical symbols and gestures akin to contemporary medicine.